IgM AUTOANTIBODIES TO DNA IN BLOOD SERUM OF THE PATIENTS WITH HEMORRHAGIC FEVER WITH RENAL SYNDROME - D. G. Ishmukhametova; B. K. Temesgen; O. V. Yakusheva (Медицинская иммунология)
Levels of IgM autoantibodies (AAbs) to native (double-stranded) and denaturated (single-stranded) DNA were studied in blood serum of sixty patients with hemorrhagic fever with renal syndrome (HFRS) and twenty-five healthy persons, using an ELISA technique. The median levels of IgM AAbs to double-stranded DNA in blood serum of healthy persons and HFRS patients corresponded to 0.41 and 0.53 arbitrary units, respectively. Thus, the difference between the samples from HFRS and healthy persons proved to be non-significant. The median level of IgM AAbs to single-stranded DNA in blood sera of HFRS patients (0.71 arbitrary units) did significantly exceed serum values of healthy persons (0.57 arbitrary units). A probable involvement of IgM AAbs into regulation of IgG AAbs' production during virus-induced activation of autoimmune events in HFRS patients is discussed.